Construction of a nomogram model for predicting the outcome of debulking surgery for ovarian cancer on the basis of clinical indicators - Si, Yuanyuan; Song, Ningjia; Ji, Yong (Frontiers in Oncology, 2024)
This study aimed to investigate the risk factors affecting satisfaction with debulking surgery for ovarian cancer and establish a preoperative clinical predictive model. Methods: Clinical data from 131 patients who underwent ovarian cancer debulking surgery at Jiangnan University Affiliated Hospital between 2016 and 2022 were collected. Patients were randomly separated into an experimental group and a control group in a 7:3 ratio. On the basis of intraoperative outcomes, patients were grouped as either surgery-satisfactory or surgery-unsatisfactory. Clinical indicators were compared through single-factor analysis between groups. Significantly different factors (P < 0.1) were further analyzed through multivariate logistic regression.A predictive nomogram model was developed and validated by receiver operating characteristic(ROC), calibration, and clinical decision curves. Results: Single-factor analysis revealed the significance of factors,such as albumin levels,alkaline phosphatase (ALP), ECOG scores, CA125, HE4,and lymph node metastasis. Multivariate regression analysis identified albumin levels, ALP, ECOG scores, HE4, and lymph node metastasis as independent risk factors for satisfactory surgical outcomes in patients with ovarian cancer undergoing debulking surgery as (P < 0.05). A clinical predictive model was successfully constructed. ROC curves showed AUC values of 0.818 and 0.796 for the experimental and validation groups, respectively. Internal validation through the bootstrap method confirmed the model's fit in both groups.Meanwhile,the clinical decision curve demonstrated the model's high utility. Conclusion:Independent risk factors associated with satisfactory tumor reduction in patients with ovarian cancer undergoing debulking surgery included decreased albumin levels, ALP > 137 U/L, ECOG = 1 score, HE4 > 140 pmol/L, and lymph node metastasis. Constructing a clinical predictive model through logistic regression analysis enables individualized testing and maximizes clinical benefits.